Pharmacological strategies for detoxification - Diaper, Alison M (Blackwell Publishing Ltd, 2014)
Detoxification refers to the safe discontinuation from a substance of dependence and is distinct from relapse prevention. Detoxification usually takes between a few days and a few weeks to complete, depending on the substance being misused, the severity of dependence and the support available to the user. Psychosocial therapies alongside pharmacological treatments are essential to improve outcome. The dependencies considered in this overview are detoxification from opioids (with methadone, buprenorphine, α(2)-adrenoceptor agonists and adjunct medications), alcohol (with benzodiazepines, anti-glutamatergics and γ-aminobutyric acid (GABA)-ergic drugs), stimulants and cannabis (with no clear recommended pharmacological treatments), benzodiazepines (with dose tapering) and nicotine (with nicotine replacement therapy, antidepressants and partial agonists). Evidence is limited by a lack of controlled trials robust enough for review bodies, and more research is required into optimal treatment doses and regimes, alone and in combination.